Prostatic Carcinosarcoma - (:unkn) unknown (My University, 2017)
Prostat karsinosarkomu, sarkomatöz ve karsinomatöz unsurlardan oluşan nadir bir malignitedir. Sıklıkla kötü prognozu olan çok agresif tümörlerdir. Bu olgu sunumunda, 3 yıl maksimum androjen blokajı alan prostat adenokarsinomu olgusunda prostat karsinosarkomu gelişen 78 yaşındaki bir erkek hasta sunuldu. Bu nadir görülen malignitenin klinik ve patolojik özelliklerini güncel bilgilerle tanımlamaya çalıştık

Prostatic carcinosarcoma is a rare malignancy composed of sarcomatous and carcinomatous elements. Predominantly, they are very aggressive tumors with a poor prognosis. In this case report, a 78 year-old male patient with prostate adenocarcinoma developing prostatic carcinosarcoma after using androgen blockade for 3 years was presented. We tried to define the clinical and pathological features of this rare malignancy with current information.
Prostat Karsinosarkomu
Keywords: Onkoloji; Üroloji ve Nefroloji